1991
DOI: 10.1007/bf00290990
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of toluene in denitrifying Pseudomonas sp.: indication for toluene methylhydroxylation and benzoyl-CoA as central aromatic intermediate

Abstract: The anaerobic degradation of toluene has been studied with whole cells and by measuring enzyme activities. Cultures of Pseudomonas strain K 172 were grown in mineral medium up to a cell density of 0.5 g of dry cells per liter in fed-batch culture with toluene and nitrate as the sole carbon and energy sources. A molar growth yield of 57 g of cell dry matter formed per mol toluene totally consumed was determined. The mean generation time was 24 h. The redox balance between toluene consumed (oxidation and cell ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Numerous laboratory and field studies have shown that hydrocarbon-degrading bacteria can participate in the degradation of many of the chemical components of jet fuel and gasoline, including the BTEX compounds (e.g., Jamison et al, 1975;Atlas, 1981Atlas, , 1984Atlas, , 1988Gibson and Subramanian, 1984;Reinhard et al, 1984;Young, 1984;Bartha, 1986;Wilson et al, 1986Wilson et al, , 1987Wilson et al, , and 1990Barker et al, 1987;Baedecker et al, 1988;Lee, 1988;Chiang et al, 1989;Grbic-Galic, 1989 andCozzarelli et al, 1990;Leahy and Colewell, 1990;Altenschmidt and Fuchs, 1991;4-35 Alvarez and Vogel, 1991;Baedecker and Cozzarelli, 1991;Ball et al, 1991;Bauman, 1991;Borden, 1991;Brown et al, 1991;Edwards et al, 1991 and1992;Evans et al, 1991a and1991b;Haag et al, 1991;Hutchins and Wilson, 1991;Hutchins et al, 1991a and1991b;Beller et al, 1992;Bouwer, 1992;Edwards and Grbic-Galic, 1992;Thierrin et al, 1992;Malone et al, 1993;Davis et al, 1994). Biodegradation of fuel hydrocarbons can occur when an indigenous population of hydrocarbon-degrading microorganisms is present in the aquifer and sufficient concentrations of electron acceptors and nutrients, including fuel hydrocarbons, are available to these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratory and field studies have shown that hydrocarbon-degrading bacteria can participate in the degradation of many of the chemical components of jet fuel and gasoline, including the BTEX compounds (e.g., Jamison et al, 1975;Atlas, 1981Atlas, , 1984Atlas, , 1988Gibson and Subramanian, 1984;Reinhard et al, 1984;Young, 1984;Bartha, 1986;Wilson et al, 1986Wilson et al, , 1987Wilson et al, , and 1990Barker et al, 1987;Baedecker et al, 1988;Lee, 1988;Chiang et al, 1989;Grbic-Galic, 1989 andCozzarelli et al, 1990;Leahy and Colewell, 1990;Altenschmidt and Fuchs, 1991;4-35 Alvarez and Vogel, 1991;Baedecker and Cozzarelli, 1991;Ball et al, 1991;Bauman, 1991;Borden, 1991;Brown et al, 1991;Edwards et al, 1991 and1992;Evans et al, 1991a and1991b;Haag et al, 1991;Hutchins and Wilson, 1991;Hutchins et al, 1991a and1991b;Beller et al, 1992;Bouwer, 1992;Edwards and Grbic-Galic, 1992;Thierrin et al, 1992;Malone et al, 1993;Davis et al, 1994). Biodegradation of fuel hydrocarbons can occur when an indigenous population of hydrocarbon-degrading microorganisms is present in the aquifer and sufficient concentrations of electron acceptors and nutrients, including fuel hydrocarbons, are available to these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratory and field studies have shown that hydrocarbon-degrading bacteria can participate in the degradation of many of the chemical components of jet fuel and gasoline, including the BTEX compounds (e.g., Jamison et al, 1975;Atlas, 1981Atlas, , 1984Atlas, , and 1988Gibson and Subramanian, 1984;Reinhard et al, 1984;Young, 1984;Bartha, 1986;Wilson et al, 1986Wilson et al, , 1987Wilson et al, , and 1990Barker et al, 1987;Baedecker et al, 1988;Lee, 1988;Chiang et al, 1989;Grbic-Galic, 1989 andCozzarelli et al, 1990;Leahy and Colewell, 1990;Altenschmidt and Fuchs, 1991;Alvarez and Vogel, 1991;Baedecker and Cozzarelli, 1991;Ball et al, 1991;Bauman, 1991;Borden, 1991;Brown et al, 1991;Edwards et al, 1991 andEvans et al, 1991a andHaag et al, 1991;Hutchins and Wilson, 1991;Hutchins et al, 1991a andBeller et al, 4-26 Bouwer, 1992;Thierrin et al, 1992;Malone et al, 1993;Davis et al, 1994). Biodegradation of fuel hydrocarbons can occur when an indigenous population of hydrocarbon-degrading microorganisms is present in the aquifer and sufficient concentrations of electron acceptors, nutrients, and electron donors such as fuel hydrocarbons, are available to these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratory and field studies have shown that hydrocarbon-degrading bacteria can participate in the degradation of many of the chemical components of fuel hydrocarbons, including the BTEX compounds (e.g., Jamison et al, 1975;Atlas, 1981Atlas, 1984Atlas, , 1988Gibson and Subramanian, 1984;Reinhard et al, 1984;Young, 1984;Bartha 1986;Wilson et al, 1986Wilson et al, , 1987Wilson et al, , and 1990Barker et al, 1987;Baedecker et al, 1988Lee, 1988Chiang et al, 1989;Grbic-Galic, 1989 and1990;Cozzarelli et al, 1990 Leahy andColewell, 1990;Altenschmidt and Fuchs, 1991;Vogel, 1991 Baedecker andCozzarelli, 1991;Ball et al, 1991;Bauman, 1991;Borden, 1991;Brown et al, 1991;Edwards et al, 1991 andEvans et al, 1991a andHaag et al, 1991;Hutchins et al, 1991a andBeller et al, 1992;Bouwer, 1992;Edwards and Grbic-Galic, 1992;Thierrin et al, 1992;Malone et al, 1993;Davis et al, 1994). Fuel hydrocarbons biodegrade naturally when an indigenous population of hydrocarbon-degrading microorganisms is present in the aquifer and sufficient concentrations of electron acceptors and nutrients are available to these organisms.…”
Section: Biodegradation Of Btexmentioning
confidence: 99%